Structural insights into the target specificity of plant invertase and pectin methylesterase inhibitory proteins - Hothorn, Michael; Wolf, Sebastian; Greiner, Steffen; Scheffzek, Klaus (The plant cell, 2004)
Pectin methylesterase (PME) and invertase are key enzymes in plant carbohydrate metabolism. Inhibitors of both enzymes constitute a sequence family of extracellular proteins. Members of this family are selectively targeted toward either PME or invertase. In a comparative structural approach we have studied how this target specificity is implemented on homologous sequences. By extending crystallographic work on the invertase inhibitor Nt-CIF to a pectin methylesterase inhibitor (PMEI) from Arabidopsis thaliana, we show an α-helical hairpin motif to be an independent and mobile structural entity in PMEI. Removal of this hairpin fully inactivates the inhibitor. A chimera composed of the α-hairpin of PMEI and the four-helix bundle of Nt-CIF is still active against PME. By contrast, combining the corresponding segment of Nt-CIF with the four-helix bundle of PMEI renders the protein inactive toward either PME or invertase. Our experiments provide insight in how these homologous inhibitors can make differential use of similar structural modules to achieve distinct functions. Integrating our results with previous findings, we present a model for the PME-PMEI complex with important implications.